Studi Tentang Penerapan Pendekatan Komunikatif dan Pendekatan Terpadu dalam Pembelajaran Bahasa Indonesia di Kelas VI SD Negeri 1 Gadung Mas Kabupaten Lombok Timur - Baharudin, Baharudin (khatulistiwa, 2020)
The purpose of this study is to describe how a communicative approach and an integrated approach are implemented in learning Indonesian in class VI SD Negeri 1 Gadung Mas. The research design used is a qualitative case study. This design was chosen because it is in accordance with the characteristics of the study, namely the case of BI learning in class VI SD Negeri 1 Gadung Mas which was carried out by a BI teaching teacher in applying the Communicative Approach and Integrated Approach. The data of this research were taken from the Learning Implementation Plan (RPP), learning implementation, and learning outcomes carried out by BI teachers for class VI at SD Negeri 1 Gadung Mas. Data were collected by (1) Questionnaire, (2) Interview, (3) Field Notes, (4) Documentation Study, and (5) Observation. The data from the learning implementation component shows the following data. All forms of PBM interactions that have been carried out by teachers have implemented PK. PBM interactions are dominated by students and all communication activities are on the part of students. The interactions that occur are two-way interactions and multi-directional interactions and the most common interactions are two-way interactions. In this PBM the teacher only functions as a communicator, motivator, and facilitator. In PBM interactions 8 times face-to-face in 4 times face-to-face the teacher has implemented PT. The rest, namely 4 face-to-face teachers have not implemented PT. The technique of presenting the material used by the teacher has applied PK. The teacher has chosen a material presentation technique that leads students to actively communicate. In addition, the teacher has created a pleasant learning atmosphere, and prepared a variety of materials, thus encouraging students to learn and use BI in real terms. Of the 8 face-to-face meetings, only 3 face-to-face teachers used the material presentation technique by applying PT. In 5 face-to-face meetings, the teacher did not use the material presentation technique that applied PT. There are 30 evaluation activities (KE) of BI teaching conducted by teachers for 8 face-to-face meetings. Of the 30 ECs, 25 EC teachers have implemented EC and 5 EC have not implemented EC. During 8 face-to-face meetings, in only 3 face-to-face meetings the teacher presented KE by applying PT. Furthermore, in 5 other face-to-face meetings, the teacher did not present the KE who applied PT.